Upregulation of ADAM12 contributes to accelerated cell proliferation and cell adhesion-mediated drug resistance (CAM-DR) in Non-Hodgkin's Lymphoma. Issue 9 (21st October 2017) - Yin, Haibing; Zhong, Fei; Ouyang, Yu; Wang, Qiru; Ding, Linlin; He, Song
ABSTRACT: Objective: ADAM12 is a member of a disintegrin and metalloproteinase family and has been reported to participate in the development of variety of tumors. However, the role of ADAM12 in Non-Hodgkin Lymphoma (NHL) has not been investigated. The present study was undertaken to determine the expression and biologic function of ADAM12 in human NHL. Methods: First, we constructed a model of cell adhesion in NHL, the mRNA, and protein level of ADAM12 in suspension and the adhesion model was analyzed by RT-PCR and western blot. Then, flow cytometry assay and western blot were used to investigate the mechanism of ADAM12 in the proliferation of NHL cells. In vitro, after using siRNA interfering ADAM12 expression, we performed adhesion assay and cell viability assay to determine the effect of ADAM12 on adhesive rate and drug sensitivity. Results: ADAM12 was lowly expressed in suspended cells and highly expressed in adherent NHL cells. In addition, ADAM12 was positively correlated with the proliferation and apoptosis of NHL cells by regulating the expression of p-AKT and p-GSK-3β. Furthermore, ADAM12 promoted cell adhesion-mediated drug resistance (CAM-DR) in DLBCL via AKT signaling pathway. Conclusion and discussion: Our data support a role for ADAM12 in NHL cell proliferation, adhesion, and drug resistance, and it may pave the way for a novel therapeutic approach for CAM-DR in NHL.